Describing undergraduate students’ reasoning and use of evidence during argumentation about socioscientific issues systems - Jimenez, P. Citlally; Alred, Ashley R.; Dauer, Jenny M. (Frontiers in Education, 2024)
We conducted research in a post-secondary, large-enrollment science literacy course that asks students to apply multidisciplinary scientific evidence when providing an argument about the potential social and ecological consequences of policy solutions to socioscientific issues (SSI).Coding schemes were developed to describe students' levels of proficiency in constructing arguments about the nature of SSI systems and were created through inductive coding of student arguments about SSI systems embedded within a structured decision-making process. The coding schemes included student practices in 1) providing reasoning about the potential consequences of multiple solutions for an SSI, 2) linking evidence to reasoning, and 3) sources of evidence. In the highest level in the reasoning coding scheme, students used clear and traceable scientific evidence to address an assumption by specifying how (a mechanism) or by how much, an SSI solution might satisfy a desired policy objective. The resulting framework describes how students apply multidisciplinary scientific evidence to support their SSI reasoning, which may aid researchers and educators in exploring how students interpret and integrate scientific evidence in an SSI-context, with the ultimate goal of bolstering students' ability to reason about evidence outside the classroom.